2011
DOI: 10.1177/0013916511410421
|View full text |Cite
|
Sign up to set email alerts
|

The Presence of a Pleasant Ambient Scent in a Fashion Store

Abstract: Marketing managers are increasingly using olfactory marketing instruments in the retail environment. However, the question is whether scents in the store are desirable for all consumer types. Research on the moderating role of individual differences on the impact of scents in the marketplace is scarce. This article focuses on how ambient fragrances in the store can influence customers’ affective, evaluative, and approach reactions and considers the moderating role of shopping motivation and affect intensity. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 88 publications
(39 citation statements)
references
References 57 publications
1
35
3
Order By: Relevance
“…This shows that a store atmosphere has the ability to affect consumers not only cognitively but also emotionally (Muhammad et al, 2014). Since consumers perceive the retail atmosphere with their senses, it is a crucial aspect of the shopping process and behavioral responses (Doucé & Janssens, 2013).…”
Section: Store Atmosphere and Gift Storesmentioning
confidence: 98%
See 2 more Smart Citations
“…This shows that a store atmosphere has the ability to affect consumers not only cognitively but also emotionally (Muhammad et al, 2014). Since consumers perceive the retail atmosphere with their senses, it is a crucial aspect of the shopping process and behavioral responses (Doucé & Janssens, 2013).…”
Section: Store Atmosphere and Gift Storesmentioning
confidence: 98%
“…Hedonic motivations are related to the consumer's emotions and experiences (Babin, Darden, & Griffin, 1994;Büttner et al, 2013). In this sense, consumers with a utilitarian motivation appreciate when a product can be bought in a deliberate and efficient way; while those with a hedonic motivation appreciate the experience of purchasing (Doucé & Janssens, 2013).…”
Section: Consuming Motivations and The Store Atmospherementioning
confidence: 99%
See 1 more Smart Citation
“…For example, people born before 1930 tend to display positive association with nature scents, and the fragrance of Playdough triggers nostalgia in those born after 1960 [6]. Scents can also influence behaviour: in shops, a pleasant scent positively impacts customers' attitude towards the store, the evaluation of products and intention to revisit the place [7]. A British company claims that treating customers with the smell of male sweat made them 17% more likely to pay their bills than a control group [8].…”
Section: Olfaction and Heritagementioning
confidence: 99%
“…For instance, a warm pink light that flatters the face and helps banish wrinkles has been used as a step further in lighting retail practice (Blumenthal, 1988). A study of Areni and Kim (1994) found that brighter in-store lighting influenced people to examine and handle more merchandise. These findings can be considered in terms of their implications for creating a functional store environment as well as an appropriate store image.…”
Section: Introductionmentioning
confidence: 99%